Development of newer catalytic systems and protocols for a few important catalysts and inorganic reagents based on cobalt (II and III), copper (II), chromium (VI), vanadium (IV and V) and Tribromide (Br3) - Dehury, Sanjay K (My University, 2004)
The present thesis is based on the results of investigation of a few chosen aspects of metal acetylacetonates, oxofluorochromates (VI), ammonium tribromides and peroxovanadates (V). It constitutes, in part, an interpretative account of solvent-less and peroxometal- mediated synthesis of metal acetetylacetonates and development of metal acetylacetonate based heterogeneous catalysts and catalytic systems to work in water. In the next part of the thesis the importance of synthesis and versatility of some chromium (VI) reagents and catalysts have been highlighted. Another part of the thesis focuses on solvent-less synthesis of quaternary ammonium tribromides and solid-phase experiments for bromine-less brominations. The concluding section presents our work on synthesis, isolation, and structural assessment of a few vanadium-peroxo-citrate complexes. The subject matter of the thesis is...
Saikia, Anil Kumar
Baruah, Jubaraj Bikash
Keywords: CHEMISTRY